Sumatra’s rubber agroforests: advent, rise and fall of a sustainable cropping system - Feintrenie, L.; Levang, P. (2009)
Until the end of the nineteenth century primary forests covered nearly all the island of Sumatra. The first valorisation of this natural resource was hunting and gathering activities, followed by and later associated with swidden cultivation of upland rice. The industrial revolution in Europe and North America in the 1950s created increasing demand for rubber. Answering this new market opportunity, farmers introduced rubber seedlings in their swiddens amidst the upland rice. By doing so, they invented a new cropping system, i.e. rubber agroforests. Thanks to the continuously increasing demand for rubber by the developing industry, rubber agroforests spread over Sumatra’s eastern peneplains until the 1990s. Forest conversion to rubber agroforests conserves a high level of forest biodiversity and the agroforests act as a buffer zone around national parks. But with growing demographic pressure, market integration and household monetary needs, agroforests are increasingly endangered. New cropping systems have appeared and challenge agroforests’ dominance in the landscape. Since the mid-twentieth century, rubber monospecific plantations have been competing for land, with an undoubtedly higher profitability than agroforests. More recently, oil palm plantations have spread over the island, quickly becoming the new challenger to rubber agroforestry. Nevertheless, the international community shows more and more interest in forest and biodiversity conservation. Forest cover in Jambi province has nearly disappeared over the past 30 years. The only way to save the remnants of forests and agroforests seems to be the creation of market incentives through conservation programs such as reducing emissions from deforestation and degradation.